Dentists' training in Chile and some iberoamerican countries. Considerations for education, health and job. - Anggelo Carrizo (Universidad de Concepción., 2014)
In the recent years many research focused on the training of dentists in Chile and other countries of Iberoamerica and its implications have been published. However, there is no analysis of all the evidence at a regional level. The aim of this article is to review the changes in the training of Dentists in Iberoamerica, the educational and/or sanitary policies associated to these changes and the impact that these have had in the future for the dentists in Chile and the region. In general terms it´s been observe a strong increase of the amount of available places for studying Dentistry in several countries of the area, without a clear sanitary or educational planning that justify it. This increment does not show and positive impact in the access to the dental treatment, especially in the poorest populations. Although the levels of dentist´s satisfaction are high, in the recent years have been observed a rise in the unemployment and a salary decrease, which could impact in the professional satisfaction. In Iberoamerica uncontrolled growth is observed in the training of dentists, which has no positive impact on the population´s oral health, but negatively to the workforce.